Stability enhancement of the integration of wind and solar energy fed to sg-based power system - Nguyen Thi Mi Sa; Truong Dinh Nhon (Journal of Technical Education Science, 2014)
This paper proposes an integrated power generation system, applying pole-placement technique, fed by three power sources: wind power, solar power, and traditional power which are connected to a commercial power system. Different power sources can be interconnected anywhere on the same power line, leading to flexible system expansion. The effective control scheme using a voltage source inverter (VSI) joined with a proportional-integral-derivative (PID) damping controller is designed to contribute adequate damping characteristics to the dominant modes of the studied system under various operating conditions. A frequency-domain approach based on a linearized system model using root-loci technique and a time-domain scheme based on a nonlinear system model subject to a three-phase short-circuit fault at the connected bus are systematically performed to examine the effectiveness of the proposed control schemes.